Ternary Cathode Blend Electrodes for Environmentally Friendly Lithium‐Ion Batteries. Issue 15 (25th June 2020) - Jobst, Nicola Michael; Hoffmann, Alice; Klein, Andreas; Zink, Stefan; Wohlfahrt‐Mehrens, Margret
Abstract: The combination of two active materials into one positive electrode of a lithium‐ion battery is an uncomplicated and cost‐effective way to combine the advantages of different active materials while reducing the disadvantages of each material. In this work, the concept of binary blends is extended to ternary compositions. The combination of three different active materials provides high versatility in designing the properties of an electrode. Therefore, the unique properties of a layered oxide, phospho‐olivine, and spinel type material are mixed to design a high‐energy cathode with improved environmental friendliness. Four different compositions of blend electrodes are investigated, each with individual benefits. Synergistic effects improved the rate capability, power density, thermal and chemical stability simultaneously. The blend electrode consisting of 75 % NMC, 12.5 % LMFP and LMO provides similar energy and power density as a pure NMC electrode while economizing 25 % cobalt and nickel. Abstract : More than the sum of its parts ! Moving from binary to ternary blends of active materials in cathode materials for lithium ion batteries provides a versatile design beyond the properties of the individual components. Synergistic effects improve the rate capability, power, thermal, and chemical stability of the blend. Overall advantageous performance is achieved while economizing 25 % cobalt and nickel of a NMC622 based electrode.